Comic Media on Force Topic in Science Lessons for Grade IV Elementary School - Ni Kadek Vilasa Devi; D.B. Kt. Ngr. Semara Putra (Indonesian Journal Of Educational Research and Review, 2022)
Learning media used in uncertain situations during pandemics such as today must have a flexible, efficient and practical nature.  This research aims to find out the feasibility of Comic media on the content of natural science grade IV elementary school style material. This type of research is development research using the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model.  Data collection uses the questionnaire method.  Validation of assessment instruments is carried out by 3 experts consisting of content experts, design experts, and media experts and 26 students on field tests. This study obtained excellent results, as evidenced by validation results by content experts, design experts, and media experts obtained scores of 93%, 97%, and 92% respectively. While for field tests obtained a score of 92%. From these results it can be concluded that this developed comic media is suitable for use on natural science material style content for grade IV elementary school. The implication of this research is that this comic media can be used in online and offline learning.